Manajemen Tata Kelola Pemerintahan Desa Wisata Berbasis Masyarakat Pada Dinas Kebudayaan Dan Pariwisata Kabupaten Toraja Utara - Maluka, Yanto; Hamzah, M. Natsir; Rukaiyah, St (STIM-LPI Makassar, 2025)
This study highlights the crucial role of government in managing tourism villages in North Toraja Regency to ensure the sustainability and success of community-based tourism. The findings indicate that supportive policies, infrastructure development, community empowerment, and effective marketing strategies enable tourism villages to become leading destinations that provide economic, social, and cultural benefits to local communities. Community-based governance significantly impacts the Department of Culture and Tourism and enhances villagers’ quality of life through cultural preservation, job creation, and local economic growth. Furthermore, the involvement of stakeholders such as local government, traditional communities, and the private sector plays a vital role in maintaining the sustainability of tourism villages. The study recommends several strategies, including capacity building through training, cultural preservation, infrastructure improvement, digital tourism promotion, multi-stakeholder collaboration, sustainable environmental management, and tourism product diversification. By implementing these strategies, tourism villages in North Toraja Regency can achieve optimal development while maintaining their cultural identity and local wisdom.